Clinical features of Behçet's disease: A retrospective chart review of 26 patients. (2nd January 2016) - Davari, Parastoo; Rogers, Roy S.; Chan, Brian; Nagler, Travis H.; Fazel, Nasim
Abstract: Background : Behçet's disease (BD) is a multi-organ inflammatory disorder with mucocutaneous, ocular, neurological, musculoskeletal, gastrointestinal, and pulmonary manifestations. The aim of this study was to determine the clinical features of BD in a cohort of patients diagnosed at the University of California, Davis, United States. Methods : The medical records of 59 patients with an ICD9-code of BD were retrospectively reviewed. The International Criteria for BD was used to identify patients with a point score ≥5. The clinical manifestations of BD were investigated over a 10-year period in this cohort. Results : Twenty-six patients (20 women, six men; female:male ratio = 3.3:1.0) had a point score ≥5 based on the International Criteria. The average age of onset of BD was 29.25 ± 14.25 years. Oral ulcers (100%), genital ulcers (84.6%), articular involvement (69.2%), ocular involvement (65.3%), and skin lesions (50.0%) were the most prevalent manifestations of BD in this cohort. Conclusion : Oral ulcers were the most common presenting and lifetime sign of BD. In our cohort, oral and genital ulcers were hallmarks of BD, independent of patient demographics. Thus, patients with these signs require close surveillance for other manifestations of the disease.